Post-Translational Modification of Lamins: Mechanisms and Functions - Zheng, Mingyue; Jin, Guoxiang; Zhou, Zhongjun (Frontiers in Cell and Developmental Biology, 2022)
Lamins are the ancient type V intermediate filament proteins contributing to diverse biological functions, such as the maintenance of nuclear morphology, stabilization of chromatin architecture, regulation of cell cycle progression, regulation of spatial-temporal genes expression, and transduction of the mechano-signaling. Deregulation of lamins is associated with abnormal nuclear morphology and chromatin disorganization, leading to a variety of diseases such as laminopathy, premature ageing, and might also play roles in cancer. Accumulating evidence indicates that lamins are functionally regulated by post-translational modifications (PTMs) including farnesylation, phosphorylation, acetylation, SUMOylation, methylation, ubiquitination, and O-GlcNAcylation that affect protein stabilization and the association with chromatin or associated proteins. The mechanisms by which these PTMs are modified and the relevant functionality become increasingly appreciated as understanding of these changes provides new insights into the molecular mechanisms underlying the laminopathies concerned and novel strategies for the management. In this review, we discuss a range of lamin PTMs and their roles in both physiological and pathological processes, as well as potential therapeutic strategies by targeting lamin PTMs.